Simulasi Penanganan Potensi Aliran Debris Gunung Sago Di Batang Tampo Kabupaten Tanah Datar, Sumatera Barat - Mairiza Mairiza; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Debris flow is the flow of mixture of water (from rain or other) with a high concentration of sediments slide down through the high slopes. Often, this flow carry large rocks and tree trunks, sliding down at high speed with great destructive force capabilities against anything in its path such as building houses or other facilities that threaten human life. Debris flow is not directly associated with volcanic eruptions, but can occur in volcanic regions and non-volcanic. Kanako 2D version 2.043 is a simulation software that is used as a tool to verify the effects of erosion control by sabo dam in the process of sediment transport during the debris flow. By using the tool, it can be estimated the occurrence of debris flows on the slopes of Mount Sago with simulation. Keyword : Debris flow, Kanako 2D, Sabo dam